EVALUATING DRIVER BEHAVIOR IN YELLOW INTERVAL AT SIGNALIZED INTERSECTIONS - HUSSEIN, NASREEN AHMED (Journal of Duhok University, 2020)
Signalized intersection is one of the most popular type of control at intersections in urban areas. Study of the elements of this type of control is vital to reduce accident rate, improve performance, and decrease delay. Yellow period is one of the parameters which has influence in performance of these type ofintersections specially accident rate. At the indication of yellow interval, when drivers approach a signalized intersection, they need either to proceed and cross the intersection or stop safely before the stop line. The objective of this study is to identify significant factors that impact driver’s decision at yellow interval in dilemma zone. Data was collected using questionnaire survey and video recording technique at two signalized intersections in Duhok city for the period of peak and off-peak hours. Assessing the effects of influential factors including vehicle speed, distance to the stop line and vehicle type on driver behavior has been achieved through observations of trends from graphs and statistical analyses using Logistic regression. Results of questionnaire survey indicate that the younger drivers of (18-30) years are more aggressive and end up running a red light. Moreover, the results of trend analysis showed that number of drivers who run the yellow decreases as the distances to stop line increases and dilemma zone at peak hours are located nearer to the stop line as compared to off peak hours. The lower green time to cycle time ratio in four leg intersection increased the probability of crossing the intersection instead to wait for another green period. Results of all three parts show that both the vehicle speed and distance to the stop line are significant factors affecting driver decision.